2016
DOI: 10.1007/s12185-016-1968-4
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a novel putative mitochondrial protein FAM210B associated with erythroid differentiation

Abstract: The transcription factor GATA-1 plays an essential role in erythroid differentiation. To identify novel GATA-1 target genes, we analyzed a merged ChIP-seq and expression profiling dataset. We identified FAM210B as a putative novel GATA-1 target gene. Study results demonstrated that GATA-1 directly regulates FAM210B expression, presumably by binding to an intronic enhancer region. Both human and murine FAM210B are abundantly expressed in the later stages of erythroblast development. Moreover, the deduced amino … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…In addition, FAM210B regulates FECH enzyme activity. Our results are consistent with and extend the findings of a recent study identifying Fam210b as a GATA1 transcriptional target that is required for erythroid differentiation (29). Mitochondrial mass, membrane potential, and porphyrin levels are normal in Fam210b Ϫ/Ϫ cells, precluding a role for FAM210B in housekeeping mitochondrial homeostasis or tetrapyrrole synthesis, respectively.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In addition, FAM210B regulates FECH enzyme activity. Our results are consistent with and extend the findings of a recent study identifying Fam210b as a GATA1 transcriptional target that is required for erythroid differentiation (29). Mitochondrial mass, membrane potential, and porphyrin levels are normal in Fam210b Ϫ/Ϫ cells, precluding a role for FAM210B in housekeeping mitochondrial homeostasis or tetrapyrrole synthesis, respectively.…”
Section: Discussionsupporting
confidence: 92%
“…Fam210b is transcriptionally activated by GATA-1 (29,56), consistent with its expression in erythropoietic tissues. Iron chelation by DFO or iron supplementation by iron citrate did not cause changes in its steady-state protein expression, indicating that FAM210B is not regulated by cellular iron status (Fig.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…A recent new study identified it as a putative mitochondrial protein using transiently transfected His/Myc-tagged FAM210B and to be involved in erythroid differentiation. 16 Our observation revealed that different cell lines express FAM210B and FAM210B was an outer membrane protein of the mitochondria with an N-terminal 47 aa MTS (Figure 4). These findings suggest that the novel mitochondrial protein FAM210B may connect mitochondrial function to cancer progression.…”
Section: Discussionmentioning
confidence: 72%
“…We next performed fluorescence-activated cell sorting (FACS) analysis to test whether coculture with OP9 cells altered the erythroid differentiation stage. During erythroid differentiation, TfR1 expression precedes GPA (also denoted CD235a) expression and subsequently decreases in the terminal stages (28). The TfR1 Ϫ GPA ϩ mature erythroid population significantly increased following the addition of SFC after coculturing in wild-type HiDEP cells (Fig.…”
Section: Resultsmentioning
confidence: 91%